The Role of Physical Activity in Adolescent Obesity: A Literature Review - Marini, Gita; Laraswati, Fira Yuniar; Mukarromah, Nur; Ananditha, Aries Chandra (Universitas Muhammadiyah Surabaya, 2022)
Background: Obesity or commonly known as overweight is a problem that is quite worrying among teenagers. Obesity in adolescence is very important to note because 80% will have a chance of obesity in adulthood. Obesity can arise from exceeded energy intake. This is compounded by a decrease in physical activity and unhealthy food. The purpose of this study is to determine the role of physical activity in adolescents with obesity. Methods: Using the Literature Review method of the role of physical activity in obese adolescents. The sources are searched via the internet with the databases of Neliti, EbscoHost, PubMed, and Atlantis Press. The keywords used are physical activity, obesity, and adolescents. This research using inclusion criteria that aim to determine the role of physical activity in obese adolescents, full text, Indonesian and English articles from 2015-2020. Ten articles are obtained. Results: Light physical activity and moderate physical activity trigger adolescents to have obesity. This happens because only a small amount of energy intake in the body is used for activities such as using technology and sedentary lifestyle behavior. Conclusion: There is a role of light physical activity and moderate physical activity in obese adolescents. The use of e-technology and sedentary lifestyle is directly related to physical activity and obesity.